2015
DOI: 10.4236/ojpm.2015.52007
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy as a Suicidal Ideation Predictor: A Population Cohort Study in Rural Japan

Abstract: Background: Self-efficacy has been widely studied in suicide, both in its causality and treatment effects. However, the evidence of causality is still ambiguous and there is a lack of generalizability. The aim of this study was to examine the relationship between self-efficacy and suicidal ideation through a population cohort study. Methods: The community-based household survey using a selfadministered questionnaire was conducted in a rural area of Japan, Happo Town, in Akita Prefecture with community resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
3
7
0
1
Order By: Relevance
“…Results of the current study also showed that Suicidal Ideation of nurses had a significant negative correlation with Self-Efficacy and Ego Strength; regarding Self-Efficacy variable, the result was consistent with the findings of Kobayashi et al (2015) [14], Nabavi et al (2017) [35], and Valois et al (2015) [36]. The high level of Self-Efficacy has a positive effect on mental health and its low level negatively affects self-esteem, and also, it is effective on the severity of depression and anxiety; and on the other hand, depression, anxiety, and low self-esteem can increase Suicidal Ideation; therefore, it can be concluded that low levels of Self-Efficacy can increase suicidal thoughts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results of the current study also showed that Suicidal Ideation of nurses had a significant negative correlation with Self-Efficacy and Ego Strength; regarding Self-Efficacy variable, the result was consistent with the findings of Kobayashi et al (2015) [14], Nabavi et al (2017) [35], and Valois et al (2015) [36]. The high level of Self-Efficacy has a positive effect on mental health and its low level negatively affects self-esteem, and also, it is effective on the severity of depression and anxiety; and on the other hand, depression, anxiety, and low self-esteem can increase Suicidal Ideation; therefore, it can be concluded that low levels of Self-Efficacy can increase suicidal thoughts.…”
Section: Discussionsupporting
confidence: 92%
“…According to this study, although depression is always emphasized as an important part in the underlying structure of Suicidal Ideation and attempt, Suicidal Ideation is much less likely experienced, even at the highest levels of depression, in individuals with high levels of Self-Efficacy [13]. In the study by Kobayashi et al (2015) Self-Efficacy, depression, and demographic factors were reported as predictors of Suicidal Ideation [14]. Ammentorp et al (2007) indicated the effect of training in communication skills on medical nurses' Self-Efficacy [15].…”
Section: Introductionmentioning
confidence: 93%
“…General self-efficacy was referred to as global confidence in one’s coping with novel situations, it warrants dealing with a variety of stressful situations and characterizes one’s social skills [ 28 ]. Our study replicates other research studies that pointed lower general self-efficacy as related with higher risk of suicide ideation, but assess it in patients with AD [ 69 , 70 ].…”
Section: Discussionsupporting
confidence: 87%
“…Other than paternal approval, self-efficacy is another important factor in reducing the risk of developing suicidal ideation. Kobayashi, Fujita, Kaneko, and Motohashi (2015) who conducted a longitudinal study found that the participants developed suicidal ideation due to their lower level of self-efficacy. They concluded that individual with high self-efficacy was two times less likely to have suicide thoughts.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%